1991
DOI: 10.1017/s0021859600077741
|View full text |Cite
|
Sign up to set email alerts
|

Use of n-alkanes for the estimation of herbage intake in sheep: accuracy and precision of the estimates

Abstract: S U M M A R YTwo experiments at Belclare, Co. Galway, in late autumn 1988, evaluated the use of herbage and dosed n-alkanes for estimating herbage intake by sheep. The first experiment examined faecal recoveries of dosed and herbage n-alkanes. The second experiment assessed the accuracy and precision of herbage intake estimates obtained using the n-alkane technique, and tested the effect of supplying n-alkanes to animals either in gelatine-capsules (containing different ratios of nalkane:cellulose fibre) or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
3
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 2 publications
5
36
3
1
Order By: Relevance
“…04) by about 20% lower than that obtained on the basis of pooled samples. This finding is not consistent with the results reported by Vulich et al [9] who showed that there were no statistically significant differences in estimations of DM intake based on individual or pooled samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…04) by about 20% lower than that obtained on the basis of pooled samples. This finding is not consistent with the results reported by Vulich et al [9] who showed that there were no statistically significant differences in estimations of DM intake based on individual or pooled samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The results reported by other authors recommend the use of various pairs of alkanes for the estimation of DM intake by cows. For instance, Smit et al [1] as well as Vulich et al [9] obtained results of high precision using alkanes C 33 /C 32 , while Estermann et al [7] alkanes C 31 /C 32 . Reeves et al [2] recommend that the estimation of DM intake from a pasture dominated by Pennisetum clandestinum should be based on a ratio of alkanes C 33 /C 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties arise from the labour requirement to hand-manufacture either paper pellets with adhered alkane or gelatine capsules, the correct frequency of dosing and the optimal timing of grab faecal sampling in relation to diurnal variation in alkane excretion [20]. Despite these setbacks results in sheep and cattle appear very promising [20,24,25,29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dove et al (1989) fed sheep with n-alkanes (C 28 and C 32 ) in the form of gelatin capsules of powder cellulose, previously added with a known amount of n-alkane dissolved with n-hexane or n-heptane, to estimate forage intake. Vulich et al (1991) developed a different method that consisted of mixing n-alkanes with solvents and powder cellulose, resulting in a homogenous suspension that, after being evaporated and dried, was inserted into gelatin capsules. Marais et al (1996) developed another technique in which particles of Pennisetum clandestinum (Hochst.)…”
Section: N-alcanos Para Estimar O Consumo Voluntário De Forragem Em Bmentioning
confidence: 99%